Analysis of Growth and Tourism Clusters in Madura - Titov Chuk's Mayvani; Rifai Afin; Alifah Rokhmah Idialis; Sariyani Sariyani (Jurnal Ekonomi dan Studi Pembangunan, 2022)
The tourism sector is one of the essential sectors that drive economic growth. There are many tourist destinations in Madura Island that have uniqueness, where the tourism is based on beaches, culture, history, and even religion. However, the existence of tourist destinations has not been widely felt by the Madurese community economically. Therefore, tourism development in Madura needs attention, considering the tourism sector plays a vital role in encouraging economic growth. This research uses scalogram analysis and K-Means Clustering analysis. The scalogram analysis consists of Location Coefficient (LC) analysis which reflects the level of importance of a facility in an area, and functional index analysis, which is used to measure the hierarchy of facilities in each district or region. Meanwhile, the K-Means Clustering analysis is intended to see the Madura tourism clusters. This study indicates that Sumenep Regency can be the centre of tourism growth in attractions, amenities, and accessibility. The analysis shows that Sumenep Regency is the closest distance to the cluster centre or can be categorized as an advanced cluster. Then, Pamekasan Regency is a less developed cluster because it is far from the cluster centre. This research provides some recommendation in increasing economic growth in Madura.